Commercial Aviation Firms and the Agricultural Sector in Chile, 1948-1973 [as Empresas de Aviação Comercial E O Setor Agropecuário No Chile, 1948-1973] [Las Empresas de Aviación Comercial y el Sector Agropecuario en Chile, 1948-1973] - Robles-Ortiz, C (Universidad de los Andes, Bogota Colombia, 2023)
Context/Objective: This article examines the role that an emerging sector of private commercial aviation firms played in the agricultural industry by providing aerial fumigation and cargo services in Chile from the post-WWII to 1973. Methodology: From a perspective centered on the formation and operation of individual firms, and using documentation from the Junta de Aeronáutica Civil (jac), newspapers, and technical bulletins, we analyze the expansion and then the contraction of this sector of private aviation firms and the results and problems of their operation in an initially lucrative and scarcely regulated market. Originality: Unlike most of the literature on the history of commercial aviation in Latin America, which focuses on the study of passenger airlines, this article examines commercial aviation’s role in economic development, specifically in the agricultural sector and its contribution to agricultural modernization. Conclusions: Despite initial legal and operational problems, like scarcity of capital and equipment, the companies proliferated rapidly, developed a fumigation capacity well over the demand level, and diversified their cargo activity both in the national territory and towards other countries. Thus, in a period in which agriculture’s lower growth and subordination to the industrialization-promoting state policy made it difficult to invest in technological innovations, private aviation firms made a significant contribution to agricultural modernization in Chile. They were the agents that carried out the rapid introduction and diffusion of one of the most important technological innovations worldwide: large-scale aerial fumigation of the principal commercial crops. © 2023, Universidad de los Andes, Bogota Colombia. All rights reserved.